Dziennikarskie formy sprawozdawczości sądowej - Gill, Norbert (My University, 2005)
The author conducts a detailed analysis of the contemporary problems pertaining to the issue of reports from the courts of justice which are published in the press, and the announcements about crimes which assume particular importance due to the mass range of the media. Next to personal participation, such reports are an equally important form of executing the principle of public access to trial coverage (including public notification about the course and results of the matter judged). In the conclusion, the author refers to the remarks of judge A. Murzynowski, former President of the Su- preme Court Criminal Chamber, who is of the opinion that there is no justice without public access and since the press increases public access to the judiciary, such access to information should be provided in the course of the entire criminal proceedings as long as the rules of criminal procedure are observed. Thus the journalists have to conform to the procedural mode of Polish courts of justice and accept the consequent limitations.
Journalistic Forms of Reporting from the Courts of Justice